Association between Fear of Falling, Balance and Functional Mobility in the Elderly (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Falling is the main problem that causes fear of falling in the elderly. Impaired balance is an important factor that causes falling. Falls Efficacy Scale-International (FES-I) is a tool to measure fear of falling, while balance condition can be measured using Biodex Balance System-SD (BBS-SD). Moreover, Timed up and Go Test (TUG) is a tool to measure functional mobility. The research aimed to determine correlation between fear of falling, balance and functional mobility in the elderly. Methods: The research was conducted in 39 elderly subjects at Outpatient Medical Rehabilitation Clinic of Dr. Soetomo General Hospital, Surabaya, Indonesia, who were measured using FES-I, BBS-SD and TUG. Results: The FES-I and BBS-SD probability values showed no correlation between fear of falling and balance, with p=0.064 (p>0.05). Moreover, the FES-I and TUG probability values also showed no correlation between fear of falling and functional mobility, with p=0.251 (p>0.05). Conclusion: There was no correlation between fear of falling, balance and functional mobility in the elderly at Outpatient Medical Rehabilitation Clinic of Dr. Seotomo General Hospital, Surabaya, Indonesia.